Immediate Intervention Effects of Standardized Multicomponent Group Interventions on People with Cognitive Impairment: A Systematic Review - Özbe, Dominik; Grässel, Elmar; Donath, Carolin; Pendergrass, Anna (Journal of Alzheimer's Disease, 2019)
Background: There is no curative medical treatment for dementia. Therefore, researchers turned their attention to nonpharmacological treatment approaches. Many reviews analyzed the efficacy of single-component interventions, but there has been no systematic review of multicomponent interventions so far.
CRIS-Team WoS Importer:2019-02-22